Effect of Upper Arm Position Changes on the Occurrence of Ipsilateral Shoulder Pain After Single-Operator Port Thoracoscopy - Ren, Dian; Zhang, Bo; Xu, Jie; Liu, Renwang; Wang, Jing; Huo, Huandong; Zhang, Hao; Zeng, Jingtong; Wang, Hanqing; Xu, Xiaohong; Lin, Mei; Xu, Song; et al. (Frontiers in Surgery, 2022)
Abstract Background: The aim of this study was to explore the factors associated with the occurrence of ISP after VATS to reduce the incidence of ISP and improve patients' quality of life. Methods: The data of patients were collected between June 2020 and August 2020 in the Department of Lung Cancer Surgery, Tianjin Medical University General Hospital. The angle of upper arm was measured intraoperatively. The patient’s postoperative shoulder function was quantified using the Constant-Murley shoulder function rating score. The proportional hazards model was applied to identify multiple influence factors. Results: A total of 140 eligible patients met criteria. At postoperative day 3, only the age influenced patients’ shoulder pain. At postoperative day 14, univariate and multivariate logistic regression analyses showed that age (odds ratio [OR]: 1.098 [1.046–1.152]; P<0.001) and upper arm Angle A (OR: 1.064 [1.011–1.121]; P = 0.018) were independent risk factors for low shoulder function scores. However, height was its protective factor (OR: 0.923 [0.871–0.977]; P=0.006). At postoperative day 42, univariate and multivariate logistic regression analyses showed that age (OR: 1.079 [1.036–1.124]; P<0.001) was a risk factor for low shoulder function scores, and height (OR: 0.933 [0.886–0.983]; P=0.009) was its protective factor. In contrast, upper arm Angle B was not statistically associated with low shoulder function scores (P>0.05). In addition, the reduction in ipsilateral shoulder scores after surgery was higher in patients with more than 113° of angle A (P=0.025). Conclusion: ISP was closely related to the angle of anterior flexion of the upper arm on the patient’s operative side intraoperatively. The increase in the degree of postoperative shoulder injury is more pronounced for an anterior flexion angle of >113°. Therefore, we recommend that the angle of anterior flexion of the upper extremity should be less than 113° intraoperatively.